Dampak Fatherless terhadap Perkembangan Anak - Putri Ayu Nabila; Khairul Arifin; Viola wulandari; Hidayani Syam (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
Fatherlessness, or the absence of a father’s role, can have a significant impact on children in Indonesia, including emotional and psychological disturbances, difficulties in social relationships, and an increased risk of negative behavior. Patriarchal culture and lack of social support can exacerbate this impact. Therefore, it is essential to raise awareness about the importance of a father’s role and provide support to children who grow up without a father. This journal uses a literature review method in its research, which involves analyzing various sources of information such as books, journals, or other previous studies. The research findings show that fatherlessness can have a significant impact on children in Indonesia, including emotional and psychological disturbances. Patriarchal culture and lack of social support worsen this impact. This research uses a literature review method and highlights the crucial role of fathers in shaping healthy personality and behavior in children.